MORANGUEIRO CULTIVADO SOB DIFERENTES CORES DE COBERTURAS EM TÚNEL BAIXO - HENSCHEL, JULIANE MACIEL (2016)
Strawberry is a crop of great economic and social importance. Its fruits are appreciated mainly by flavor and nutraceutical potential. The light quality affects plant physiology and can bring benefits to crops. Thus, changes in incident light spectrum can improve the development, production and fruit quality. This study evaluated effects of covers of different colors in low tunnels for strawberry crop. Were tested four colored covers (red, yellow, blue and green) and two witnesses already used commercially (transparent and milky). Were used a cultivar of short photoperiod (Camarosa) and a neutral photoperiod (Albion). The experiment was evaluated in two seasons, and in the first season were evaluated production and vegetative growth, and the second time the photosynthetic efficiency and post-harvest quality. Overall, Camarosa showed higher vegetative growth, lower production, and better quality fruit. The covers have changed the microclimate regarding shading and temperature, and influenced most of characteristics evaluated. However, the colored covers were not higher than those used commercially.